Estimation of Spleen Size With Hand‐Carried Ultrasound. (1st July 2014) - Lee, Mitchell; Roberts, J. Mark; Chen, Luke; Chang, Silvia; Hatala, Rose; Eva, Kevin W.; Meneilly, Graydon S.
Abstract : Objectives: Physical examination can identify palpable splenomegaly easily, but evaluating lesser degrees of splenomegaly is problematic. Hand‐carried ultrasound allows rapid bedside assessment of patients. We conducted this study to determine whether hand‐carried ultrasound can reliably assess spleen size. Methods: Patients with varying degrees of splenomegaly were studied. Two sonographers blindly measured spleen size in each patient using either a hand‐carried or conventional ultrasound device in random order. Sonographers completed a data sheet indicating the adequacy of the image, clinical measurements of enlargement, and confidence in their observations. Results: Sixteen patients (10 male and 6 female; mean age ± SEM, 60 ± 4 years) were recruited. Image quality was adequate or better in all scans with conventional ultrasound and in 15 of 16 scans with hand‐carried ultrasound. The greatest longitudinal measurement recorded was statistically equivalent across ultrasound techniques, with mean values of 16.4 cm (95% confidence interval, 14.8–18.0 cm) for conventional ultrasound and 15.8 cm (95% confidence interval, 14.1–17.4 cm) for hand‐carried ultrasound. The correlation between measurement techniques was r = 0.89 ( P < .0001). Sonographers were somewhat or very confident in the outcomes of all scans with conventional ultrasound and in 15 of 16 cases with hand‐carried ultrasound. In general, it took longer for sonographers to obtain images with hand‐carried ultrasound. Conclusions: We have shown that hand‐carried ultrasound can be used at the point of care by trained individuals to diagnose splenomegaly. However, hand‐carried ultrasound images were less likely to be judged excellent, were accompanied by less diagnostic certainty, and took longer to obtain.